(untitled) (Conferencea, 2022)
At the higher stages of the development and improvement process, society acquires the appearance of a complex system consisting of authorities and governing bodies covering many social rules and groups. The components of society are reminiscent of a comprehensive social organism that is closely connected with each other both horizontally and vertically. During this period, it is important for the society to ensure its stability, security and development.